(untitled) (Bangladesh Heart Journal, 2022)
Background: This cross sectional observational study was carried out with an aim to find out in-hospital outcome in patients with ST-T changes in non-STsegment elevation myocardial infarction (NSTEMI). Methods: This cross sectional observational study was carried out in the department of cardiology, National Institute of Cardiovascular Diseases, Dhaka, Bangladesh from January 2014 to December 2014. A total of 120 patients with NSTEMI were the study population. Patients were divided into two groups on the basis of ST-T changes, 60 patients with ST-T changes were in group I and 60 patients without ST-T changes were in group II. Result: In this study, the mean age was 54.2 ±14.2 years. Male female ratio was 2.75:1 among the study population. There was no statistically significant difference in mean BMI among the two groups. Smoking was the most common risk factor present (47.5%). Smoking was found significantly more in Group I than patients of group II (p=0.02). Serum troponin I was found significantly raised in group I (42.8±5.5 vs 10.5±8.3, p=0.002). The mean left ventricular ejection fraction (LVEF) of patients in group I was significantly lower than group II (52.1±9.1% vs 61.7±6.9%. p=0.001). Adverse in-hospital outcome was significantly more in group I than group II (48.3% vs 26.7%, p=0.01). Recurrent angina pectoris, STEMI, significant arrhythmia, acute LVF and cardiogenic shock were also more in group I than in group II. In-hospital mortality was noted in group I patients with both ST segment depression and T wave inversion (6.7%). Emergency revascularization was done more commonly in patients of group I (6.7%). The mean duration of hospital stay was statistically significant between the groups (6.24±2.58 vs 4.44±1.71 days. p<0.05)). Multivariate logistic regression analysis revealed that ST-T changes are an independent predictor for developing adverse inhospital outcome in patients with non-ST-segment elevation myocardial infarction. Conclusion: The ST-segment depression and T-wave inversion on admission ECG are important predictors of outcome in patients with NSTEMI. The ST-segment depression on admission ECG of patients with NSTEMI is associated with higher adverse in hospital outcome and mortality. Bangladesh Heart Journal 2022; 37(2): 99-106